2018
DOI: 10.1002/cpt.1056
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Pharmacodynamics in Healthy Volunteers Treated With GDC‐0853, a Selective Reversible Bruton's Tyrosine Kinase Inhibitor

Abstract: GDC-0853 is a small molecule inhibitor of Bruton's tyrosine kinase (BTK) that is highly selective and noncovalent, leading to reversible binding. In double-blind, randomized, and placebo-controlled phase I healthy volunteer studies, GDC-0853 was well tolerated, with no dose-limiting adverse events (AEs) or serious AEs. The maximum tolerated dose was not reached during dose escalation (≤600 mg, single ascending dose (SAD) study; ≤250 mg twice daily (b.i.d.) and ≤500 mg once daily, 14-day multiple ascending dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 30 publications
0
58
0
1
Order By: Relevance
“…The pharmacokinetics (PK) of fenebrutinib was characterized previously in healthy subjects in a Phase 1 trial, and plasma concentrations peaked 1-3 h after oral administration and declined thereafter, with a steady-state half-life ranging from 4.2-9.9 h (22). In the Phase 1 trial, fenebrutinib plasma exposures were found to increase approximately doseproportionally with modest accumulation following twice daily dosing.…”
Section: Bruton's Tyrosine Kinase (Btk) and Fenebrutinibmentioning
confidence: 96%
See 1 more Smart Citation
“…The pharmacokinetics (PK) of fenebrutinib was characterized previously in healthy subjects in a Phase 1 trial, and plasma concentrations peaked 1-3 h after oral administration and declined thereafter, with a steady-state half-life ranging from 4.2-9.9 h (22). In the Phase 1 trial, fenebrutinib plasma exposures were found to increase approximately doseproportionally with modest accumulation following twice daily dosing.…”
Section: Bruton's Tyrosine Kinase (Btk) and Fenebrutinibmentioning
confidence: 96%
“…Fenebrutinib (GDC-0853, RG7845) is an orally administered BTK inhibitor that is highly selective and noncovalent, leading to reversible binding, intended to block B cell proliferation and the resulting excessive immune response seen in autoimmune disorders (21). Fenebrutinib has previously been evaluated in healthy subjects (22) and patients with resistant B cell lymphoma or chronic lymphocytic leukemia (23).…”
Section: Bruton's Tyrosine Kinase (Btk) and Fenebrutinibmentioning
confidence: 99%
“…The dosing regimens of fenebrutinib were selected based on pharmacokinetic/pharmacodynamic modeling of BTK inhibition based on results from ascending dose studies in healthy subjects (16) with the goal of achieving plasma concentrations reaching at least IC 70 , as this extent of inhibition was correlated with efficacy in a rat collagen-induced arthritis model (15).…”
Section: Methodsmentioning
confidence: 99%
“…Fenebrutinib appears unique due to its high selectivity (for BTK versus nontarget kinases) relative to other BTK inhibitors as well as its noncovalent binding mode (15). Phase I clinical studies have shown fenebrutinib to be well-tolerated with no safety signals precluding further clinical development (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro cellular potency of fenebrutinib was determined to be 11 nM for the inhibition of BTK autophosphorylation in human whole blood obtained from healthy subjects. Additionally, target engagement has been demonstrated in a multiple ascending dose study in healthy subjects, where a maximal inhibition above 90% was seen in BTK autophosphorylation and basophil assays (Herman et al, 2018).…”
Section: Introductionmentioning
confidence: 97%